Anatomical variations of human sphenoid sinus in terms of volume and septation pattern in a subset of Pakistani population using computed tomographic images - Aijaz, Asma; Naheed Khan; Sahar Mubeen; Binish Rasheed (Journal of the Pakistan Medical Association, 2022)
Objectives: To compare the sphenoid volume between the genders and to analyse variations in septal insertions on bony wall of optic nerve and internal carotid artery. Methods: The prospective study was conducted from October 2020 to February 2021 at the Radiology Department of Dow University of Health Sciences, Karachi, and comprised paranasal sinus patients of either gender aged 20-60 without any bony deformity of sphenoid sinus who were analysed for sphenoid volume, number of septa and variable septal insertions using computed tomography of paranasal sinus. On the basis of septal insertions, the scans were categorised into Group 1 with no risky septal insertion, Group 2 with septal insertion on bony wall of optic nerve, Group 3 with septal insertion of internal carotid artery, and Group 4 with septal insertion on both optic nerve and internal carotid artery. Differences in sphenoid volume were analysed between males and females and among the four groups. Data was analysed using Graph Pad Prism 9. Results: Of the 300 patients, 171(57%) were males and 129(43%) were females. The overall mean age was 39.28±10.9 years. Multiple septa were found in 208(69.3%) of the sinuses. There were 129(43.7%) patients in Group 1, 34(11.3%) in Group 2, 119(39%) in Group 3 and 18(6%) in Group 4. Significant difference was found between volume and gender as well as among the four groups (p<0.001). Conclusion: The sphenoid volume between the genders and the variations in septal insertions on bony wall of optic nerve and internal carotid artery were significantly different.